Inverse problem for diffusion operators on the finite interval - Sat, Murat; Panakhov, Etibar S. (Amer Inst Physics, 2014)
In this paper, we discuss the inverse problem for diffusion operators on the finite interval ([0,pi]). For a fixed (n (n=0,1,2,...)), we show that the potential function (q(x)) can be uniquely determined by the spectral sets {lambda(n) (q, H-k)}(k=1)(+infinity)
10th International Conference on Mathematical Problems in Engineering, Aerospace and Sciences (ICNPAA) -- JUL 15-18, 2014 -- Narvik Univ Coll, Narvik, NORWAY
Keywords: Differential Pencils; Uniqueness Theorem; Reconstruction